Ukraine Data on Prognostic Factors and Treatment Outcomes in Patients with Peripheral T-Cell Lymphomas - Skrypets, T; Novosad, O; Pastushenko, Y; Gorbach, O; Kriachok, I (Klinicka onkologie, 2019)
BACKGROUND: Peripheral T-cell lymphomas (PTCLs) is a diverse group of lymphomas (10-15% of all non-Hodgkins lymphomas) with aggressive behavior. Despite the standard of 1st line anthracycline-containing regimens, clinical outcomes are poor compared to B-cell lymphomas. In addition, there are still debates about specific prognostic factors (PF) in PTCLs. AIMS: Primary endpoints - event-free survival (EFS) and overall survival (OS). To evaluate the prognostic significance of five PTCLs scores (International Prognostic Index - IPI, International Peripheral T-cell lymphoma Project Score - IPTCL, Prognostic Index for T-cell lymphoma - PIT, modified Prognostic Index for T-cell lymphoma - mPIT and T-cell score). PATIENTS AND METHODS: From 67 enrolled patients, only 50 were included: PTCL not otherwise specified (22, 44%), anaplastic large cell lymphoma ALK+ (anaplastic lymphoma kinase-positive) (10, 20%) and ALK (anaplastic lymphoma kinase-negative) (18, 36%). Patients received CHOP-like regimens (CHOP, CHOEP, EPOCH). RESULTS: The overall rate response was observed in 66% of cases (complete response 78%). There were 48% of relapses after the 1st line therapy during follow-up (median 11 months; range 1-85 months). Median age 57 (range 22-80) with male predominance 62%. In total, 40% of patients were > 60 years old, 48% had stage III-IV. Majority of patients were assessed by five prognostic scores. IPI (45 patients): the 3-year EFS and OS were higher for IPI 1 vs. IPI > 2 (80 vs. 18% and 87 vs. 27%, respectively; p = 0.0002). Receiver operating characteristic analysis confirmed poor clinical outcome to patients with PF > 1 (Se = 88 %; Sp = 68 %; AUC = 0.7; p = 0.0081). IPTCLP (41 patients): the presence of PF = 1-2 showed EFS and OS reduction. A 3-year EFS rate for 1-2 PF was 25 vs. 70% for PF = 0 (p = 0.003). Thus, 3-year OS in patients with PF = 0 vs. PF = 1-2 was 100 vs. 20% (p = 0.0001). PIT (42 patients): better 3-year EFS and OS in patients with PF = 0 vs. PF = 1-3 (88 vs. 28% and 100 vs. 34%, respectively, p = 0.001). Patients with PF = 1-3 have a higher rate of relapses vs. PF = 0 (p = 0.0005 by Cox-test). mPIT (21 patients): no significant difference between PF and clinical outcomes. T-cell score (18 patients): higher survival rates with PF 2. More than 2 PF have an impact on EFS (p = 0.005). The 3-years OS in patients with PF 2 was 77 vs. 25% in cases with PF 3 (p = 0.001). CONCLUSION: IPI, PIT, IPTCLP are still very useful in defining risk stratification. As to mPIT and T-cell score, more patients to evaluate their prognostication possibility are needed.
Keywords: senioři; analýza přežití; peripheral T-cell lymphomas; senioři nad 80 let; periferní T-buněčný lymfom; Ukrajina; Survival Analysis; Prognosis; prognostic factors; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Ukraine; Aged, 80 and over; Young Adult; anaplastic lymphoma kinase-positive; ženské pohlaví; prognóza; Humans; lidé středního věku; peripheral T-cell lymphomas not otherwise specified; Lymphoma, T-Cell, Peripheral; dospělí; anaplastic lymphoma kinase-negative; Female; Aged; lidé; Male